A study of the dynamics of academic performance of UNI students - Araujo, José (2019)
The education is a relevant factor in the social and economic development of a country. In 2000, the World Bank stressed that in the history, poverty or wealth of nations depends on the higher education’s quality.In this sense, the main objective of this project is to contribute on the understanding of the dynamics of the academic performance from the students of the National Uni-versity of Engineering. This contribution is valuable for the scientific community and, above all, for the creators of educational policies, since with a greater understanding of student’s issue, the educational policies can be focused and channeled more effectively.